The Impact of User Satisfaction in the Use of E-Learning Systems in Higher Education: A CB-SEM Approach - Idkhan, A. Muhammad; Idris, Muh. Ma'ruf (International Journal of Environment, Engineering and Education, 2023)
The primary objective of this research is to thoroughly investigate the intricate dynamics and collective influence of essential elements within the e-learning domain. Examining the interdependencies and combined effects of technology system quality, information quality, and support services on user satisfaction. This study investigates the key factors affecting user satisfaction in e-learning at Universitas Negeri Makassar, focusing on the roles of Information Quality, System Quality, and Service Quality. Survey data from 231 diverse students were analyzed using a Likert scale questionnaire, with Structural Equation Modeling via IBM AMOS. The findings aim to reveal how these quality dimensions impact user satisfaction, potentially guiding enhancements in e-learning system design. A comprehensive study examining e-learning systems conclusively found that System Quality, Information Quality, and Service Quality are pivotal factors influencing user satisfaction. Improving system functionality, ensuring the accuracy and relevance of information, and delivering high-quality service were all significantly correlated with higher satisfaction levels among users. This underscores the critical need for educational institutions to prioritize these aspects to enhance the e-learning experience. The research presents strong evidence that educational institutions can significantly boost user satisfaction by focusing on the quality of the system, information, and services provided in e-learning platforms. These findings provide actionable insights for decision-makers in the education sector, suggesting that investments in these areas will likely yield positive outcomes in user engagement and satisfaction with e-learning systems.